Acute toxicity of the synthetic pyrethroid deltamethrin to fingerling European catfish, Silurus glanis L. - Köprücü, SS; Köprücü, K; Ural, MS (Springer, 2006)
[Abstract Not Available]
Keywords: Fresh-Water Catfish; Cyprinus-Carpio L.; Heteropneustes-Fossilis; Trout; Organisms